Characteristic of peri urban traffic / Syazwani Zainal - Zainal, Syazwani (2006)
This study investigated the peri urban area. Butterworth and Bukit Mertajam, two major towns in Pulau Pinang, were selected as a case study area. For each zone, cross-sectional data on traffic accidents, vehicle-kilometres of travel, population, zone area, land-use developments, and street network variables were collected. Car following method were applied in order to identify peri urban boundary in terms of traffic movement. Further traffic studies such as collection of traffic volume and crash data were carried out in the peri urban area. Analyses of traffic data were conducted to develop relationships that could have practical applications for use by city planners and traffic safety engineers. The results indicated that the traffic volumes in peri urban area are low but the accident rates in peri urban area are high. In the near future a detailed traffic study should be conducted in peri urban area to minimize the congestion and accident rate in urban area.